1996
DOI: 10.1159/000185005
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Modifications in the Regulation of the Hypothalamic-Pituitary-Thyroid Axis

Abstract: We studied the hypothalamic-pituitary-thyroid function in two groups of healthy elderly subjects: group A (n = 23, age range 65-80 years), and group B (n = 11 age range 81-92 years), and in 32 controls, aged 20-60. A TRH test for TSH and prolactin was performed in all subjects, while the TSH circadian modulation was evaluated in elderly subjects only. Group B showed significantly lower fT3 and TSH, and higher fT4 levels with respect to controls (fT3: 4.4 ± 0.2 vs. 5.2 ± 0.2 pmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Accordingly, older people have lower TSH responses to thyrotropinreleasing hormone stimulation than do young people. In the oldest olds, the nocturnal surge of TSH is partially or completely lost, whereas the inhibitory effect of corticosteroids is attenuated (23,31).…”
Section: Thyroid Hormones and The Aging Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, older people have lower TSH responses to thyrotropinreleasing hormone stimulation than do young people. In the oldest olds, the nocturnal surge of TSH is partially or completely lost, whereas the inhibitory effect of corticosteroids is attenuated (23,31).…”
Section: Thyroid Hormones and The Aging Processmentioning
confidence: 99%
“…However, there exist conflicting results concerning age-related serum TSH variations between earlier studies (mainly case-control or crosssectional) and recent large naturalistic studies (3, 16, 17, 19 -23). Former studies showed either unchanged or reduced serum TSH values along with declining FT 3 concentrations in healthy elderly humans (especially the oldest old), with low serum T 3 associated with better physical performance and higher lean body mass (16,17,23,24). This condition has been interpreted as an adaptive mechanism to prevent excessive catabolism and should be distinguished from the so-called "nonthyroidal illness syndrome" (frequently observed in older people), in which serum FT 3 decreases while FT 4 (within the normal range of healthy adults) and rT 3 (above the normal range of healthy adults) increase (25).…”
Section: Thyroid Hormones and The Aging Processmentioning
confidence: 99%
“…Hypothalamic TRH content is reduced in aged rats [32,35] and thyrotroph response to TRH is mostly reported as decreased, both in rats [29,32,36] and [37,38] in humans. Non-stimulated TSH concentration has also been reported as relatively diminished by aging in a large population of older persons without hyperthyroidism, and in aging patients with resistance to thyroid hormone (and their non-affected relatives) [27].…”
Section: Aging and Hypothalamus-pituitary-thyroid Axismentioning
confidence: 98%
“…Indices of the hypothalamic±pituitary±thyroid axis function in ageing individuals indicate a high incidence of thyroid hormone de®ciencies with normal or increased serum TSH, decreased stimulated TSH secretion, decreased sensitivity of the thyroid gland to TSH, impaired feedback control of T3 on pituitary thyrotrophs, decreased productive or releasing capacities of the thyroid gland and decreasing serum levels of T3 in ageing man, monkey and rat (Hesch et al, 1976;Harman et al, 1984;Drinka and Nolten, 1988;Monzani et al, 1996). T4 and T3 production rates are decreased in older rats and did not increase during overfeeding as observed in young adult rats (Katze, 1990).…”
Section: Ageing and Hormonal Balancementioning
confidence: 99%